O modelo langackeriano como instrumento para a análise da linguagem de crianças portadoras de paralisia cerebral e possibilidades para uso terapêutico - Flavia Felipe Silvino (2006)
Cognitive Linguistics and, in particular, Ronald Langackers (2001) theoretical model of Linguistic Meaning Construction assume that language forms an integral part of human cognition and is inherently symbolic in nature. The present study aimed at verifying the use of this model as a therapeutic tool to analyze the communicative process of children with Quadriplegic Cerebral Palsy and, thus, identify the way they create and use strategies to construct and signify their communicative process. This model was applied to the video-recording analyses of the interaction of three patients aged four to six years old during speech therapy sessions. These children were selected given that they presented communicative intention behaviors, namely, face-to-face interaction and gaze and/or gesture directing toward the interlocutor aiming at turning the other participants attentional to their attentional focus in the scene. The use of Langackers model evidenced its effectiveness as a tool to analyze interactions and as a fundamental basis for professionals particularly involved in improving the patients body stance, identifying strategies to demonstrate the patients communicative intention and recognizing the body movements with symbolic function.